Comparison of Gain In Length After Post Burn Contracture Release By Z-Plasty And Square Flap - Naseem, Aiman; Faisal Akhlaq; Hyder Ali; Usamah bin Waheed; Erum Naz; Maryam Noor (Pakistan Armed Forces Medical Journal, 2024)
Objective: To compare the mean differences in gain in length after post-burn contracture release by z-plasty and square flap. Study Design: Case Series Place and Duration of Study: Plastic and Reconstructive Surgery Department, Dr Ruth KMPfau Civil Hospital, Karachi Pakistan, from Apr to Sep 2021. Methodology: Sixty patients were divided as Z-plasty and square flap groups. The length of the contracture zone was measured. Z-plasty was performed to improve the functional and cosmetic appearance of the scar. A square flap was made to release the contracture. Splintage was maintained for two weeks after its release. Results: The mean contracture length three weeks after Z-plasty release was 7.12±4.14cm and 15.39±4.66cm in square flap. Significant mean differences among techniques were observed among contracture length (p=0.001) and gain in length (p=0.001). The cubital fossa was the most common region treated with Z-plasty, while the finger was the most common region treated with square flap. The results showed a highly significant association of regions with respect to surgical techniques (p=0.001). An insignificant association was observed between gender (p=0.436) and cause of burn (p=0.136). Conclusion: The square flap technique provides greater length gains than a Z-plasty technique.